Pengaruh Kompensasi, Kepuasan, dan Lingkungan Kerja terhadap Kinerja Karyawan Departement Contract Maintenance PT. Kaltim Prima Coal - Pradigdo Wijayanto; Sukisno S. Riadi; Ariesta Heksarini (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2016)
This study aimed to analyze the Influence of compensation satisfaction, and the Working Environment on employee performance Department Contract Maintenance Pt. Kaltim Prima Coal The study population was all employees at Department Contract Maintenance Pt. Kaltim Prima Coal The number of employees is 60 employees working in the division with samples taken by 59 employees. With simple random sampling method used in this study with questionnaires randomly to the population. Data were collected using a questionnaire to provide a list of direct questions to respondents. Data analysis techniques in this study using multiple regression analysis that operates with SPSS 18 program. The results showed that compensation had significant positive effects on employee performance , satisfaction has a significant positive effect on the performance of employees, and the environment has a significant positive effect on employee performance.Keywords : Compensation, Satisfaction, Work Environment